Comparison of permeability correlations for different rock fabric - Nasr, N.H. (Medwell Journals, 2017)
Estimation of rock permeability (k) is an important aspect of petroleum engineering, often accomplished by using correlations based on water saturation or pore configuration or both. However, utilizing a correlation to determine k without knowing the pore configuration of the rock for which the correlation was originally developed can yield ambiguous results. An erroneous k can lead to incorrect reservoir performance estimation and improper development plans. This study demonstrates the need for defining the pore configuration in order to select a specific model for k estimation with a greater degree of confidence. To accomplish this, thin section petrography and petrophysical properties of several rock samples were analyzed. The measured k values of these rock samples were compared with the k values estimated from several published correlations. The accuracy of each correlation as compared to the measured values was categorized on the basis of rock fabric. Thus, an intuitive guideline was developed as to which correlations are applicable to a given rock. © Medwell Journals, 2017.